Gestión de residuos químicos en instituciones educativas - Ramos Rincón, Jaidith M; Peña Prieto, Luis E (Revista Científica, 2007)
The present article shows the relation of the educative institutions and the environmental and social responsibilities due to hazardous waste generated in laboratories. Laboratories' hazardous waste should be disposed in a manner meeting local and state regulations. This article sets the standard for the beginning of the development of the project "Dangerous and ordinary design of a plan of handling of the chemical substances, remainders generated in the building of laboratories of Macarena B of the Distrital University"